PHANGS-HST catalogs for ∼100,000 star clusters and compact associations in 38 galaxies: I. observed properties - Maschmann, Daniel; Lee, Janice C.; Thilker, David A.; Whitmore, Bradley C.; Deger, Sinan; Boquien, Médéric; Chandar, Rupali; Dale, Daniel A.; Wofford, Aida; Hannon, Stephen; Larson, Kirsten L.; Leroy, Adam K.; et al. (The astrophysical journal. Supplement series, 2024)
We present the largest catalog to date of star clusters and compact associations in nearby galaxies. We have performed a V-band-selected census of clusters across the 38 spiral galaxies of the PHANGS-Hubble Space Telescope (HST) Treasury Survey, and measured integrated, aperture-corrected near-ultraviolet-U-B-V-I photometry. This work has resulted in uniform catalogs that contain ∼20,000 clusters and compact associations, which have passed human inspection and morphological classification, and a larger sample of ∼100,000 classified by neural network models. Here, we report on the observed properties of these samples, and demonstrate that tremendous insight can be gained from just the observed properties of clusters, even in the absence of their transformation into physical quantities. In particular, we show the utility of the UBVI color-color diagram, and the three principal features revealed by the PHANGS-HST cluster sample: the young cluster locus, the middle-age plume, and the old globular cluster clump. We present an atlas of maps of the 2D spatial distribution of clusters and compact associations in the context of the molecular clouds from PHANGS-Atacama Large Millimeter/submillimeter Array. We explore new ways of understanding this large data set in a multiscale context by bringing together once-separate techniques for the characterization of clusters (color-color diagrams and spatial distributions) and their parent galaxies (galaxy morphology and location relative to the galaxy main sequence). A companion paper presents the physical properties: ages, masses, and dust reddenings derived using improved spectral energy distribution fitting techniques.
Online veröffentlicht: 9. Juli 2024
Gesehen am 17.02.2025